2017
DOI: 10.5530/jams.2017.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Phytochemical and Antioxidant Properties of Costus pictus and C. speciosus

Abstract: Introduction: C. pictus, known as spiral ginger, an ornamental plant which has its origin in Mexico, but cultivated in Indian state of Kerala. C. speciosus could be collected from its natural habitat, but due to ruthless and indiscriminate collection it is endangered. These species are used in many of the indigenous preparation, mainly known for anti-diabetic and anti-hyperlipidaemic properties. The current study is an attempt to compare the phytochemical and antioxidant potential of the two species. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The ethanol and acetone leaf extract of Hellenia speciosa showed positive for tannins, saponins, flavonoids, quinones, glycosides, cardiac glycosides, terpenoids, phenols, coumarins, steroids, alkaloids, betacyanin except for anthocyanin. Similar findings were reported from the rhizomes of Costus speciosus 22,23 and leaves of Costus pictus 24,25 . The phenols and flavonoids present in the plant extract could protect living organisms against reactive oxygen species 26,27 .…”
Section: Discussion: Phytochemical Screening Of Leaf Extract Ofsupporting
confidence: 85%
“…The ethanol and acetone leaf extract of Hellenia speciosa showed positive for tannins, saponins, flavonoids, quinones, glycosides, cardiac glycosides, terpenoids, phenols, coumarins, steroids, alkaloids, betacyanin except for anthocyanin. Similar findings were reported from the rhizomes of Costus speciosus 22,23 and leaves of Costus pictus 24,25 . The phenols and flavonoids present in the plant extract could protect living organisms against reactive oxygen species 26,27 .…”
Section: Discussion: Phytochemical Screening Of Leaf Extract Ofsupporting
confidence: 85%
“…The developed plates were visualized in UV 254, 366nm and then derivatised with vanillin sulphuric acid reagent and scanned under UV 254, 366 nm following derivatisation. Rf, colour of the spots and densitometric scan were recorded [17] .…”
Section: Hptlc Finger Printingmentioning
confidence: 99%
“…Prabhu et al found that the corrosion of 6063 aluminum alloy in NaOH media was more serious than in H 3 PO 4 media, and the corrosion rate increased with the concentrations of H 3 PO 4 and NaOH. 14 Similarly, Hsu et al found that the material removal rate of aluminum decreased with the increase of pH value of acidic polishing slurry. 15 Wang et al proposed that in acidic media, material removal in the non-passivating region (pH < 4) is a competition among passivation, mechanical wear and chemical etching.…”
mentioning
confidence: 94%